Including the effects of pressure and stress in thermodynamic functions. Issue 1 (19th December 2013) - Hammerschmidt, T.; Abrikosov, I. A.; Alfè, D.; Fries, S. G.; Höglund, L.; Jacobs, M. H. G.; Koßmann, J.; Lu, X.‐G.; Paul, G.
Abstract Most applications of thermodynamic databases to materials design are limited to ambient pressure. The consideration of elastic contributions to thermodynamic stability is highly desirable but not straight‐forward to realise. We present examples of existing physical models for pressure‐dependent thermodynamic functions and discuss the requirements for future implementations given the existing results of experiments and first‐principles calculations. We briefly summarize the calculation of elastic constants and point out examples of nonlinear variation with pressure, temperature and chemical composition that would need to be accounted for in thermodynamic databases. This is particularly the case if a system melts from different phases at different pressures. Similar relations exist between pressure and magnetism and hence set the need to also include magnetic effects in thermodynamic databases for finite pressure. We present examples to illustrate that the effect of magnetism on stability is strongly coupled to pressure, temperature, and external fields. As a further complication we discuss dynamical instabilities that may appear at finite pressure. While imaginary phonon frequencies may render a structure unstable and destroy a crystal lattice, the anharmonic effects may stabilize it again at finite temperature. Finally, we also outline a possible implementation scheme for strain effects in thermodynamic databases.